Можности за користење на искуствата на Европската Унија во поддршката на малите и средните претпријатија и претприемништвото во Р. Македонија - Крстевска, Мартина (Економски факултет, УКИМ, Скопје, 2013)
The paper is devoted to the importance of small and medium-sized enterprises (SMEs) and entrepreneurship, as an integral part of the world global economic processes, based on knowledge and innovation. The importance of EU SMEs and entrepreneurship can be seen from the fact that SMEs and entrepreneurship were at the "heart" of the Lisbon Strategy. To integrate successfully into the world global processes, for the Republic of Macedonia it is particularly important to strengthen the policy that support SMEs, as well as to strengthen the existing measures of support and to enrich tham with new ones, in order to establish a knowledge-based society. The main goal of this paper is to summarise and synthesise the policies, measures and instruments that support SMEs and entrepreneurship in the EU member states, such as: business incubators, technological parks, business networks etc. Тhis paper will elaborate the programs that support entrepreneurship, selecting those measures that support entrepreneurship in the EU and would be applicable in the Republic of Macedonia, but still do not exist. The analysis of the European best practices and the transfer of experience and knowledge from developed European countries, can serve as a basic to profile the policy that support the SMEs and the entrepreneurship in the Republic of Macedonia, thus creating stimulative business environment in the country.
Opportunities for using the European Union experiences to support SMEs and entrepreneurship in the Republic of Macedonia
Докторска дисертација одбранета во 2013 година на Економскиот факултет во Скопје, под менторство на проф. д–р Таки Фити.
Keywords: small and medium-sized enterprises, entrepreneurship, the Lisbon Strategy, policies supporting SMEs and entrepreneurship, business incubators, technological parks, business networks, the European Union, the Republic of Macedonia